Analysis of Differences in Profit Before and During the Covid-19 Pandemic in Companies Listed on the Indonesia Stock Exchange - Beni Suhendra Winarso; Dewi Amalia; Indah Kurniawati (East Asian Journal of Multidisciplinary Research, 2022)
In Indonesia itself, the pandemic has been felt since the implementation of large-scale social restrictions (lock down) since March 16 2020. The existence of this large-scale social restriction policy has had a profound impact on various sectors including the industrial sector. This research was conducted by comparing proximate profitability to earnings per share before and during the pandemic in companies that distributed dividends. Analysis was carried out using an independent sample t-test by testing the normality of the residual data first. Data during the pre-pandemic window period were 271 companies from 2017-2019 which is the three-year mean EPS and during the 2020 pandemic there were 263 companies. The results of the descriptive statistical test showed a minimum EPS of -395.50, a maximum of 4,578.13, a mean of 159.57 before the pandemic and during the pandemic a minimum of -1,043.45, a maximum of 3,974.73 and a mean of 83.98.